Innate Lymphocytes in Adipose Tissue Homeostasis and Their Alterations in Obesity and Colorectal Cancer - Del Cornò, Manuela; Conti, Lucia; Gessani, Sandra (Frontiers in Immunology, 2018)
Colorectal cancer (CRC) is the third most common cancer worldwide and a leading cause of death, with burden expected to increase in the coming years. Enhanced adiposity, particularly visceral fat, is associated with increased cancer incidence representing an important indicator of survival, prognosis, recurrence rates, and response to therapy for several tumors including CRC. Compelling evidence has been achieved that the low-grade chronic inflammation characterizing obesity represents a main factor that can favor carcinogenesis. Adipocytes and adipose tissue (AT) infiltrating immune cells contribute to obesity-related inflammation by releasing soluble factors affecting, both locally and systemically, the function of several cell types, including immune and cancer cells. The unbalanced production of immune mediators as well as the profound changes in the repertoire and activation state of immune cells in AT of obese subjects represent key events in the processes that set the basis for a pro-tumorigenic microenvironment. AT harbors a unique profile of immune cells of different origin that play an important role in tissue homeostasis. Among these, tissue-resident innate lymphocytes are emerging as important AT components whose depletion/aberrant activation occurring in obesity could have an impact on inflammation and immune-surveillance against tumors. However, a direct link between obesity-induced dysfunction and cancer development has not been demonstrated yet. In this review, we provide an overview of human obesity- and CRC-induced alterations of blood and adipose tissue-associated innate lymphocytes, and discuss how the adipose tissue microenvironment in obesity might influence the development of CRC.